2022
DOI: 10.3390/md20100640
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Medicinal Resources through Marine Soft Coral Aquaculture: Insights into the Chemical Diversity and the Biological Potential

Abstract: In recent decades, aquaculture techniques for soft corals have made remarkable progress in terms of conditions and productivity. Researchers have been able to obtain larger quantities of soft corals, thus larger quantities of biologically active metabolites, allowing them to study their biological activity in many pharmacological assays and even produce sufficient quantities for clinical trials. In this review, we summarize 201 secondary metabolites that have been identified from cultured soft corals in the er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In addition, the two most bioactive compounds, glaucumolide A ( 5 ) and glaucumolide B ( 6 ), were obtained with relatively high quantity, measured at 31.59 mg and 53.98 mg, respectively. The results suggested that aquaculture of soft coral could be a prolific and sustainable resource for the drug discovery and development [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the two most bioactive compounds, glaucumolide A ( 5 ) and glaucumolide B ( 6 ), were obtained with relatively high quantity, measured at 31.59 mg and 53.98 mg, respectively. The results suggested that aquaculture of soft coral could be a prolific and sustainable resource for the drug discovery and development [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds were found to be effective in the inhibition of elastase release with IC 50 values of 18.8 and 6.9 µM. Lobovarol I (38), a new prenyleudesmane-type diterpene isolated from the same sample of the soft coral, inhibited the release of elastase with an IC 50 value of 20 µM. The other known eudesmane derivative (39) was found to be active with IC 50 values of 13.7 µM and 4.4 µM in superoxide anion generation and elastase release assays, respectively [91] (Figure 8).…”
Section: Miscellaneous Diterpenesmentioning
confidence: 99%
“…Several chemical studies conducted on Rumphella antipathies led to the isolation of bioactive sesquiterpenes, including clovan-2,9-dione (1), antipacid B (2), and Aquaculture of soft corals has been conducted since the late 1950s for the purposes of commercialization and preservation. Many techniques, such as coral gardening, microfragmentation, larval enhancement, and direct transplantation, have been developed to meet the demand for the mass production of soft corals [38]. Ex situ and in situ are current approaches to coral cultivation.…”
Section: Sesquiterpenes and Derivativesmentioning
confidence: 99%
“…Every year, thousands of newly isolated marine natural products are reported [ 1 , 2 ]. These metabolites provide a wide range of bioactivities, including anti-cancer, anti-viral, anti-bacterial, anti-fungal and anti-inflammatory abilities [ 1 , 2 ]. These natural products are primarily isolated from marine microorganisms, algae and invertebrates.…”
Section: Introductionmentioning
confidence: 99%